If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(8 + x) = 6 (8 * 6 + x * 6) = 6 (48 + 6x) = 6 Solving 48 + 6x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 6x = 6 + -48 Combine like terms: 48 + -48 = 0 0 + 6x = 6 + -48 6x = 6 + -48 Combine like terms: 6 + -48 = -42 6x = -42 Divide each side by '6'. x = -7 Simplifying x = -7
| 2x^2+3x=4 | | 14x+32=70 | | 6x-6-3x=-18 | | 6(-11+2n)-2n=-7(-n+3) | | 2(6+7x)=68 | | 0.75a+14=8 | | 5t-4=4+t | | 5(6x-10)=-20 | | (8a^2-6a-8)-(-6a^2+7a+5)= | | 4(n-6)-(2-3n)=6n | | 4x+1=34+7x | | (x-2)(x+6)=3x | | 3x+30=81 | | x^2+24x-112=0 | | -y=-x-4 | | b^2=2b | | t(t-7)=18 | | x^2-x+649=0 | | -2(x+5)+4x= | | -10-2x=x+5 | | y=x^2+3x-5 | | 10x-3x-9+3-x=18 | | 17x-8=12x+33 | | 4x-1=3x+4 | | 20t^2=64+64t | | 2x+7=4x+7 | | 4x^2-7x+13=6x+3 | | 5k-4k+6= | | 20t^2=64+64 | | 10+3y=-9 | | 6x^2-38x-80=0 | | -2c+12=2c-6+6c-12 |